Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Persamaan Linear Dua Variabel - Lisa, Chairil; Baidullah, Baidullah (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to analyze the understanding of eighth-grade students at SMP Negeri 1 Jeumpa regarding the material on linear equations with two variables. The research subjects consisted of 13 students, and the primary instrument used was a test as the main data and interviews as supporting data. The results showed that 40% of the students had a low level of understanding, indicating significant difficulties in comprehending and applying basic concepts. The study concludes that more interactive and supportive teaching methods are needed to enhance students' understanding of linear equations with two variables. Keywords : analysis, ability, understanding, PLDV